Review of the microheterogeneous thoria-urania fuel for micro-sized high temperature reactors - Rabir M.H.; Ismail A.F.; Yahya M.S. (John Wiley and Sons Ltd, 2023)
Nuclear fuels; Pelletizing; Pressurized water reactors; Thoria; Thorium; Uranium dioxide; Blanket configurations; Economic performance; Inherent characteristics; Micro-heterogeneous; Power distributions; Reactor designs; Systematic Review; Thermal margins; High temperature reactors